Spatio‑Temporal Model of Extreme Rainfall Data in the Province of South Sulawesi for a Flood Early Warning System - Bakri, Bambang; Adam, Khaeryna; Rahim, Amran (Geomatics and Environmental Engineering, 2021)
In this study, we model extreme rainfall to study the high rainfall events in the province of South Sulawesi, Indonesia. We investigated the effect of the El Nino South Oscillation (ENSO), Indian Ocean Dipole Mode (IOD), and Madden‑Julian Oscillation (MJO) on extreme rainfall events. We also assume that events in a location are affected by events in other nearby locations. Using rainfall data from the province of South Sulawesi, the results showed that extreme rainfall events are related to IOD and MJO.